2014
DOI: 10.5688/ajpe786125
|View full text |Cite
|
Sign up to set email alerts
|

Use of Virtual Patients in an Advanced Therapeutics Pharmacy Course to Promote Active, Patient-Centered Learning

Abstract: Objective. To assess student satisfaction and learning of course objectives following the integration of virtual patient cases designed to promote active, patient-centered learning in an advanced therapeutics pharmacy course. Design. A dynamic virtual patient platform that incorporated a branched-narrative, decision-making teaching model was used in an advanced therapeutics course to supplement lecture content. Assessment. Presimulation and postsimulation tests were used to assess student learning. The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 8 publications
1
54
0
Order By: Relevance
“…In addition to online modules, online virtual patients are used in educating health professionals, 21,22 with increased use in pharmacy education over the last decade. [23][24][25][26][27][28][29][30][31] Virtual patient programs allow learners to gain experience by making and learning from decisions in a safe environment, 25 thus supporting the active experimentation stage of experiential learning theory. 32 The inclusion of "scenario-based" virtual patient programs can be effective where strategic, rather than procedural, learning goals are required.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to online modules, online virtual patients are used in educating health professionals, 21,22 with increased use in pharmacy education over the last decade. [23][24][25][26][27][28][29][30][31] Virtual patient programs allow learners to gain experience by making and learning from decisions in a safe environment, 25 thus supporting the active experimentation stage of experiential learning theory. 32 The inclusion of "scenario-based" virtual patient programs can be effective where strategic, rather than procedural, learning goals are required.…”
Section: Introductionmentioning
confidence: 99%
“…More than 60% of respondents conveyed that their institutions have no clearly defined policy regarding cell phone use during class; the decision is at the discretion of individual instructors to determine course directives. A small number of respondents (7,8.3%) in our study reported they do not have a cell phone policy.…”
Section: Single College Of Pharmacy Surveymentioning
confidence: 82%
“…[4][5][6][7] Other research has focused on faculty and students' satisfaction and perceived effectiveness of educational technologies utilized in pharmacy education. [8][9][10][11][12][13] Technology appears to be changing the pharmacy educational environment and creating opportunities for learning.…”
Section: Introductionmentioning
confidence: 99%
“…As in the previous studies, receiving immediate feedback, accessing exercises without a geographical or temporal limitation, providing a safe environment, and practicing processing a prescription were identified as useful features of MyDispense. 8,[17][18][19][20] Like many simulation programs, MyDispense has a limited scope of simulation as it does not simulate hospital pharmacy practice or an authentic interaction with other health care providers and patients. When implementing a simulation in a course, course directors should consider its useful features and limitations to determine the best way for its incorporation.…”
Section: Discussionmentioning
confidence: 99%